2-layer Cable-in-Conduit for Hybrid-Coil Magnets. Issue 1 (March 2020) - Breitschopf, J; Chavez, D; Elliott, T.; Kellams, J; McIntyre, P; Sattarov, A
Abstract: Recent results are reported in the development of 2-layer cable-in-conduit (SuperCIC) that is designed for use in hybrid-coil magnets. SuperCIC preserves the full performance of the individual wires, and can be formed into flared-end windings for dipoles into layer-wound toroids and solenoids for hybrid windings for tokamaks. The structure of the SuperCIC windings is designed to accommodate winding and heat-treating sub-windings of Bi-2212, Nb3Sn, and NbTi separately and then assembling them and preloading in the magnet.